2014
DOI: 10.1109/tap.2014.2327642
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation Method for the Probability Distribution of the Quality Factor of Mode-Stirred Reverberation Chambers

Abstract: An efficient experimental technique is presented for determining the empirical probability distribution of the quality factor ( ) of a mode-stirred reverberation chamber. The method is based on triplets of S-parameters that are measured at three locations of the receiver and spectrally averaged across a narrow frequency interval. It avoids the need for detailed spatial mechanical scanning of a field sensor. Statistics of the fluctuations of the stored and dissipated energy can be deduced individually. The effe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…Although the antennas exhibit considerable impedance mismatch at the lowest and highest measurement frequencies over these wide bands, previous analysis has shown that this mismatch is of little significance in considering the ratios of S-parameter-based quantities [20], pertinent to the present analysis. …”
Section: A Measurement Configurationmentioning
confidence: 96%
See 1 more Smart Citation
“…Although the antennas exhibit considerable impedance mismatch at the lowest and highest measurement frequencies over these wide bands, previous analysis has shown that this mismatch is of little significance in considering the ratios of S-parameter-based quantities [20], pertinent to the present analysis. …”
Section: A Measurement Configurationmentioning
confidence: 96%
“…Complex S-parameter data were measured in a 8.7 × 3.7 × 2.9 m 3 mode-stirred reverberation chamber [20] (first resonance at f 110 43.8 MHz), from 40 MHz to 5.040 GHz with a 125-kHz sampling step, using a pair of identical log-periodic antennas (M = 1000 equiangular stir steps), and again from 100 MHz to 12 GHz, now with a 150-kHz sampling step using a pair of identical broadband dipole antennas (1400 stir steps). Although the antennas exhibit considerable impedance mismatch at the lowest and highest measurement frequencies over these wide bands, previous analysis has shown that this mismatch is of little significance in considering the ratios of S-parameter-based quantities [20], pertinent to the present analysis.…”
Section: A Measurement Configurationmentioning
confidence: 99%
“…μw,rf πμ0σw (18) in which Q∞ Δ = 3hV /(2μw,rδwS) represents the asymptotic quality factor for f → +∞ [14]. In summary, the limit distribution of Δ is a normal distribution N (μΔ, σΔ), i.e.,…”
Section: Theoretical Pdfmentioning
confidence: 99%
“…The resulting empirical cdf FΔ(δ) is compared with the theoretical F (4M, 6M ) cdf (9). Multivariate spectral averaging for evaluating FQ(q) based on measured S-parameters has previously been described, developed, and validated in [18]. It is applied here to the empirical determination of F Δ(δ).…”
Section: A Measurementmentioning
confidence: 99%
See 1 more Smart Citation